Fabrication of single piece definitive obturator for post surgical maxillectomy defect during covid-19 pandemic- A Literature review with Clinical case report (Bangladesh Journal of Medical Science, 2022)
Background: Impacts of primary oncology surgical procedure can impede restoration objectives. Restoring oral function, comfort and aesthetics is a challenge due to limitations in the restorative treatment options.Methodology: Literature review on the responsibilities, role of maxillofacial prosthodontist, materails and retentive aids used for prosthesis, classification of maxillofacial prostheses, recent advancements in MFP and Workflow for the fabrication of obturator prostheses in the COVID-19 pandemic scenario. Case report on the fabrication of Holllow bulb definitive obturator during pandemic crisis. A 47 years old male patient reported for post-surgical evaluation in maxillary posterior region of oral cavity. The patient had partial maxillectomysurgical procedure of squamous cell carcinoma in the palate 5 years back. To replace the gap created, the patient was using interim obturator. He had facial asymmetry and collapse. Prosthodontic rehabilitation with one piece closed hollow bulb obturator was planned & subsequently fabricated for the patient. For our case considering the feasibility & ease of manipulation, heat activated acrylic resin was used for this particular patient for rehabilitation. The method described is easy, simple, time saving & economical. Bulb portion was hollow & made of heat cure resin, so weight was less & less chances of tissue irritation.Results: With the Covid-19 infection protocol measures taken definitive obturator was given to the maxillectomy patient to restore aesthetics, function and comfort as well. After insertion of prostheses mastication, deglutition and phonetics were improved. Breathing problems were resolved and aesthetics was improved.Conclusion: A simplified technical approach for the treatment of a patient with palatal defect of and other supportive structure has been presented in Covid-19 situation following the described infection prevention protocols. The technique presented offers a method of obtaining a detailed impression of the defect and promptly provides the patient with a light weight, easyto- use and flexible tissue- tolerant obturator.Bangladesh Journal of Medical Science Vol. 21 No. 04 October’22 Page : 676-684